Pengaruh Kualitas Pelayanan dan Store atmosphere Terhadap Keputusan pembelian pada Toko Roti Ganda Pematangsiantar - Nisa Fadillah; Dina Sarah Syahreza (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the influence of service quality and store atmosphere on purchasing decisions at Toko Roti Ganda in Pematangsiantar. Using a quantitative approach, data were collected through questionnaires distributed to 140 respondents who are customers of Toko Roti Ganda. The questionnaire was designed to measure customer perceptions of service quality and store atmosphere, as well as their impact on purchasing decisions. The analysis results indicate that good service quality, which includes aspects of reliability (score 3.81), friendliness, and responsiveness, has a significant impact on customer satisfaction and purchasing decisions, with a t-value of 5.352 and a significance level of 0.000. Additionally, an attractive store atmosphere, including elements such as lighting, layout (score 3.45), and aroma, also positively influences purchasing decisions, with a t-value of 5.957 and a significance level of 0.000. This research provides valuable insights for the management of Toko Roti Ganda to enhance service quality and store atmosphere, thereby attracting more customers and increasing their satisfaction. The findings are expected to contribute to the existing literature on the influence of service quality and store atmosphere in the context of the culinary business.